관현악단 전문 연주자와 대학생 연주자의 연주 관련 근골격계 증상의 발생 특성에 관한 비교 - 신혜원; 김선엽 (대한정형도수물리치료학회지, 2022)
Background: Instrument players are exposed to occupational musculoskeletal symptoms due to constant movement and strain to meet the needs of their audience. This can cause dissonance between the player and the instrument and can cause medical problems in the musculoskeletal system such as pain, tendinitis, muscle spasms, and joint hyperextension from overuse of body parts. Objective: The purpose of this study is to comparatively analyze the characteristics and occurrence of musculoskeletal symptoms in professional and student players, and to find out the awareness of the need for health care professionals and special exercise programs for orchestra players. Methods: The subjects were professional orchestral musicians 191 from the three symphony orchestras and music students 209 from the four universities volunteered to participate in this study; 393 subjects (98.25%) completed the questionnaire. symptom prevalence and related factors of playing-related musculoskeletal disorders (PRMDs) were surveyed with a self-administered questionnaire. Standardized Nordic Questionnaire was complemented by adding a visual-among scale and used to diagnose PRMD. Results: High prevalence of musculoskeletal complaints in both professional musicians (85.30%) and student musicians (82.30%). Professional musicians and student musicians also suffered the highest problem in shoulder and neck complaints. Significant differences were found between groups that recognized of necessity for specialized health professionals, professional organizations, and special programs for musicians. Conclusions: Professional musicians and student musicians, like orchestra players, are already exposed to overuse syndrome. However, student musicians lack awareness of the risk of injury compared to orchestra players. We suggest that an appropriate treatment management program for the prevention and early treatment of musculoskeletal system damage should be provided to performers at an early stage.